eran Guru Bimbingan Dan Konseling Dalam Upaya Perencanaan Karir Siswa Kelas XI Multimedia SMKN 1 Kalijambe - Sabrina, Fadila (MEDI KONS: Jurnal Prodi Bimbingan dan Konseling UNISRI Surakarta, 2023)
This study aims to: 1) To find out how the career planning implementation program at SMKN 1 Kalijambe, 2) To find out what obstacles arise during the career planning implementation program at SMKN 1 Kalijambe, 3) To find solutions to problems that arise related to the program. implementation of career planning at SMKN 1 Kalijambe, 4) To find out how the role of BK teachers at SMKN 1 Kalijambe in carrying out career planning, especially for class XI Multimedia students. The method used in this study is a qualitative descriptive method, using data analysis by Miles and Huberman. Meanwhile, to assess the validity or level of confidence of the data presented, the next step is to use triangulation of sources from three different sources. Based on the results of research at SMKN 1 Kalijambe that the implementation of BK at SMKN 1 Kalijambe has been carried out optimally and directed. Constraints that arise during the implementation of Career Counseling at SMKN 1 Kalijambe are more dominant from students who do not know their potential and lack of knowledge about career information. The solution given by the BK teacher is to continue to provide the counseling services that students need to help optimize their career planning process. The role of a BK teacher in students' career planning efforts is that they have been given motivational support, insight and provided facilities to develop every potential possessed by their students so that students are able to prepare themselves to plan future careers after graduating from SMK N 1 Kalijambe. Keywords: Guidance Teacher.and.Counseling,Planning.Career